2021
DOI: 10.1186/s13018-021-02480-9
|View full text |Cite
|
Sign up to set email alerts
|

Logistic regression analysis on risk factors of augmented vertebra recompression after percutaneous vertebral augmentation

Abstract: Objective To explore the high-risk factors of augmented vertebra recompression after percutaneous vertebral augmentation (PVA) in the treatment of osteoporotic vertebral compression fracture (OVCF) and analyze the correlation between these factors and augmented vertebra recompression after PVA. Methods A retrospective analysis was conducted on 353 patients who received PVA for a single-segment osteoporotic vertebral compression fracture from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…The presence of non-PMMA-endplate-contact might play an essential role in inducing recompression after PKP treated vertebrae [ 9 ]. In addition, the distance between PMMA and endplate was an important risk factor for the recompression of cemented vertebrae after PKP, and the recompression of cemented vertebral height was positively correlated with the distance between PMMA and endplate [ 23 ] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of non-PMMA-endplate-contact might play an essential role in inducing recompression after PKP treated vertebrae [ 9 ]. In addition, the distance between PMMA and endplate was an important risk factor for the recompression of cemented vertebrae after PKP, and the recompression of cemented vertebral height was positively correlated with the distance between PMMA and endplate [ 23 ] .…”
Section: Discussionmentioning
confidence: 99%
“…It has a broad consensus that recompression of an augmented vertebra could frequently occur after PVP, and the probability of recompression is increasing with the increasing application of PVP [ 9 , 10 ]. The representative risk factor associated with recompression after PVP is osteoporosis; other factors associated with the vertebral height loss include the cemented volume, advanced age, bone mineral density, the distribution pattern of cement injected into the fractured vertebra, and contact between bone cement and upper-lower endplates [ 9 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cancellous bone in this area is susceptible to collapse under prolonged stress. Therefore, the strength of the vertebrae is positively correlated with the rate of contact between the bone cement and the upper and lower endplate [11]. When the bone cement was injected into the vertebrae with adequate dispersion, the risk of postoperative refracture would reduced.…”
Section: Discussionmentioning
confidence: 99%
“…However, statistics show that the rate of new vertebral compression fractures in patients after PKP was approximately 8.7%-18.4% [3][4][5][6], which makes postoperative refracture an important issue for clinicians. Previous retrospective studies have reported several possible risk factors for refracture, including associations between age, body mass index (BMI), clinical complication rate, bone mineral density (BMD), number of initial surgical segments, and surgical puncture method [3,[6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%